Pogledi na subjektiviteto in govorca v trubadurski liriki - Balžalorsky, Varja (Primerjalna književnost, 2007)
The article approaches troubadour poetry from the perspective of subjectivity and the lyrical speaker, by analysing some of the most representative approaches to this topic, which represent various temporal and methodological moments of the past thirty years.
Keywords: francoska književnost; French literature; medievistika; trubadurska lirika; lirski subjekt; srednjeveška estetika; literarna recepcija; glasba; music